Morphological and Physical Fitness Differences in Young Soccer Players According to Playing Position: A Systematic Review [Diferencias Morfológicas y de Condición Física en Futbolistas Adolescentes Según Posición de Juego: Una Revisión Sistemática] - Herrera-Valenzuela, T (Asociacion Espanola de Dietistas-Nutricionistas, 2021)
Introduction: The aim of this systematic review was to analyze the studies that evaluate morphological and physical fitness differences in young soccer players according to playing position. Material and Methods: For its elaboration, the PRISMA-P protocol was followed, the PubMed/MEDLINE database was used, and the Downs & Black methodological quality assessment was applied. Six studies met all the selection criteria, adding 784 soccer players (229 defenders [DF]; 271 midfielders [MF], 168 forwards [FW] and 69 goalkeepers [GK]) with a mean age of 16.2 years. Results: The analyzed studies indicate, that GK and DF have a height, body weight, endomorphic component and body fat higher than MF and FW, except for one study that reports higher values for body weight in FW and DF with respect to MF. In relation to physical fitness, the maximum squat exhibited higher values for FW compared to MF; cardiorespiratory fitness was higher in DF and MF when compared with GK and abdominal muscle resistance was greater in MF compared to DF. Conclusion: The GK and DF show greater height, body weight and body fat than the MF and FW. While physical fitness indicates that FW show greater lower body strength, MF and DF achieve greater cardiorespiratory fitness and MF present greater abdominal muscle resistance when young soccer players are analyzed according to playing position. © 2021 Asociacion Espanola de Dietistas-Nutricionistas. All rights reserved.